Development of mathematics teaching materials: Internalizing Al-Qur'an, Hadith, Madurese culture, and religious moderation - Dewi Rosikhoh (Fakultas Tarbiyah Universitas Ibrahimy, 2024)
The existence of a mandate from the Ministry of Religion regarding the integration of religious knowledge and science, as well as the internalization of religious moderation in every subject in class, had implications for the movement to develop learning media. One form of learning media was teaching materials. This development research aimed to design a fraction of teaching materials based on the al-Qur'an and hadith with internalizing religious moderation and Madurese culture for grade V elementary schools in Pamekasan and then test its validity. This research was development research using the ADDIE model. Meanwhile, testing the validity of teaching materials used expert and practitioner validation with questionnaire instruments. The research results showed that based on validation questionnaires for material experts, learning experts, Islamic religious experts, and practitioners, the teaching materials developed could be categorized as valid with an average score of 92%. Thus, teaching materials could be continued at the trial or field test stage. Apart from that, similar teaching materials could be developed on other mathematics topics at the elementary level, or similar teaching materials could be produced on the same issues but by internalizing the culture of each region.